Strengthening adolescent health literacy through a student-led vaping programme - Azmi, Muhammad Fairuz; Hykal, Rydah; Muaddib Razaly, Muhammad ‘Ammar; Zulkefli, Haikal Zuhdi; Mohammad Niza, Muhammad Ihtisyam; Musa, Aisya Natasya (Faculty of Medicine, 2025)
The rising prevalence of vaping among Malaysian teenagers continues to present a significant challenge to public health efforts. Recognising this trend, a group of Year 2 medical students, Rydah Hykal, Muhammad ‘Ammar Muaddib Razaly, Haikal Zuhdi Zulkefli, and Muhammad Ihtisyam Mohammad Niza, designed and delivered a structured awareness programme for 80 Form 4 students at Sekolah Department of Anatomy, & Year 2 MBBS students from Group 46 Pre-Clinical Elective Programme 2024/2025, Department of Medicine (Respiratory Unit)Menengah Kebangsaan Desa Cempaka, Negeri Sembilan. Guided by their supervisor, Dr. Muhammad Fairuz Azmi, this initiative formed part of their Pre-Clinical Elective and aimed to strengthen students’ understanding of the health risks associated with vaping.